(untitled) (Journal of Entrepreneurship and Business, 2021)
The study aims to investigate the social entrepreneurial intentions of university students in Pampanga, Philippines. Particularly, it scrutinizes the significant differences in the respondents? social entrepreneurial intentions when grouped based on five (5) demographic factors namely: nationality, age, year level, sex, and exposure to student leadership. The participants of the study were randomly selected from three (3) private higher education institutions, one (1) state university, and one (1) local college in Pampanga, Philippines. All these five (5) higher education institutions offer business and entrepreneurship curricular programs. A descriptive research design was used in the study and Mann- Whitney U and Kruskal-Wallis H tests were employed to examine the research hypotheses. The results revealed that the students? nationality and age showed no statistical significant difference with their social entrepreneurial intentions. On the other hand, sex, year level, and exposure to student leadership reflected significant differences with social entrepreneurial intentions. The findings suggest that nationality and age are insignificant factors affecting the respondents? social entrepreneurial intentions while sex, year level, and exposure to student leadership are significant variables. Implications of the study and the directions for future research were also identified.